Pemutusan Hubungan Kerja oleh Pengusaha - Rahayu, Sandi; Purnamawati, Linda (LAW REVIEW, 2002)
Termination of employment, in any of its forms, is a very crucial, even the most important  issue in human resource field. Practically, this means that such employee would be jobless and consequently lose his/her source of income, a state which often lead to future miseries. Although practically employees deserve any right to terminate their employment relationship, in practice such termination is often initiated by the employers.  Therefore there is no doubt that termination of employement by the employers play major  role in any employment relationship. This paper aims to answer several research questions which cover: a. Terms used to define various termination of employment and its possible causes. b. Justification of employment termination, improper termination and its sactions. c. Prevailing regulations on termination of employment. d. Differences between termination individual and group of employees (mass termination). e. Basis for termination of employment. f. Emlpoyers responsibilities and duties in the termination of employees doing major mistakes. g. Action and performances being categorized as major mistakes which legally lead employers to terminate employment. h. Procedurs for termination of employment.